Sanksi Kebiri Kimia Bagi Pelaku Kejahatan Seksual terhadap Anak (Analisis Undang-Undang Nomor 35 Tahun 2014 Studi Komparatif Hukum Pidana di Indonesia dan Hukum Pidana Islam) - Bob Friandy (Justicia Islamica, 2017)
In Indonesia, cases of sexual crimes have increased every year, the victims are not only adults, but now they have spread to teenagers, children, and even toddlers. The phenomenon of sexual crimes against children is increasingly common and has become global in almost every country. Cases of sexual crimes against children continue to increase from time to time. The increase is not only in terms of quantity or the number of cases that occur, but also in terms of quality. More tragically, the perpetrators are mostly from the family environment or the environment around the child, including in his own home, school, educational institutions, and the child's social environment.